中国民间资本问题研究 = A study on private capital in China - 韩冬艳 Han, Dongyan (2008)
This dissertation analyzes China’s non-government finance. Firstly, we estimate the scale of this new phenomenon, and then point out the restrictions which can affect the effects of the non-government finance. We conclude that during the economic development of China, the non-government sector plays an important role.